2019
DOI: 10.1016/j.xphs.2018.10.045
|View full text |Cite
|
Sign up to set email alerts
|

Steric Repulsion Forces Contributed by PEGylation of Interleukin-1 Receptor Antagonist Reduce Gelation and Aggregation at the Silicone Oil-Water Interface

Abstract: Silicone oil, used as a lubricating coating in pharmaceutical containers, has been implicated as a cause of therapeutic protein aggregation. After adsorbing to silicone oil-water interfaces, proteins may form interfacial gels, which can be transported into solution as insoluble aggregates if the interfaces are perturbed. Mechanical interfacial perturbation of both monomeric recombinant human interleukin-1 receptor antagonist (rhIL-1ra) and PEGylated rhIL-1ra (PEG rhIL-1ra) in siliconized syringes resulted in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 71 publications
0
10
1
Order By: Relevance
“…The potential for aggregation is also higher in the non-PEGylated protein as PEGylation has been shown to reduce aggregation. 16,17 These results are in contrast to our previous research using IgG ab2GPI antibodies where significant inhibitory potential of DI was retained but not enhanced after PEGylation. 13 The strongest inhibition was seen in those patients with both high IgA aDI/ab2GPI and high IgG aDI/ab2GPI.…”
Section: Discussioncontrasting
confidence: 96%
“…The potential for aggregation is also higher in the non-PEGylated protein as PEGylation has been shown to reduce aggregation. 16,17 These results are in contrast to our previous research using IgG ab2GPI antibodies where significant inhibitory potential of DI was retained but not enhanced after PEGylation. 13 The strongest inhibition was seen in those patients with both high IgA aDI/ab2GPI and high IgG aDI/ab2GPI.…”
Section: Discussioncontrasting
confidence: 96%
“…71,72 Biophysical characterization methods such as intrinsic fluorescence quenching and circular dichroism have shown that perturbations in protein structure may occur after protein adsorption to silicone oilewater interfaces presented by these droplets. 40,43,65 Owing to interference caused by the aromatic and chiral nature of DEHP, we could not use these same biophysical characterization methods to probe possible structural perturbations in proteins at the DEHP-water interface. Instead, we showed that IVIG adsorbed strongly to DEHP nanodroplets, resulting in surface coverages similar to those previously reported for monoclonal antibodies at the silicone oilewater interface.…”
Section: Effect Of Dehp and Silicone Oil Nanodroplets On Ivig Stabilitymentioning
confidence: 99%
“…Furthermore, IL-1ra gels at DEHP-water interfaces exhibited more variability in strength compared with those at the silicone oilewater interface. 43,53 A slower rate of gelation combined with weaker gels could explain reduced rates of IVIG aggregation in formulations containing DEHP nanodroplets compared to rates in formulations containing silicone oil nanodroplets.…”
Section: Effect Of Dehp and Silicone Oil Nanodroplets On Ivig Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…1,2,[5][6][7][8][9][10] Over several years, John Carpenter and Ted Randolph have published hundreds of valuable and fundamental insights into the many ways solution conditions and solution handling can lead to high viscosity, which impairs manufacturing, as well as to aggregation, that can compromise safety and efficacy of biopharmaceutics. [11][12][13][14][15][16][17][18][19][20][21][22][23] A common feature of their research is the underlying presence of protein-protein interactions that lead to unwanted outcomes.…”
Section: Introductionmentioning
confidence: 99%